Income Tax Rates, Tax Sanctions and Modernization of Tax Services on Taxpayer Compliance in Magetan Regency – Indonesia - Naufalfa'iq, Muhammad Maulid; Nugroho, Sasmito widi; kurniawan, Yopie diondy (Summa : Journal of Accounting and Tax, 2024)
The phenomenon of taxpayer compliance is a critical issue in a country's taxation system. This compliance refers to the willingness and actions of taxpayers to fulfill their tax obligations in accordance with applicable regulations. The level of taxpayer compliance is influenced by various factors, both encouraging and inhibiting. This research aims to analyze the influence of Income Tax (PPh) rates, tax sanctions, and modernization of tax services on taxpayer compliance in Magetan Regency. This research uses a quantitative approach with interview and questionnaire methods targeting taxpayers registered at the Magetan Tax Service, Counseling and Consultation Office (KP2KP). A total of 120 questionnaires were collected and analyzed using multiple regression analysis techniques with the help of IBM SPSS 24. Several tests carried out included data quality tests, classical assumption tests, and hypothesis tests. The research results show that partially, income tax rates, tax sanctions and modernization of tax services have a positive and significant influence on the level of taxpayer compliance in Magetan Regency. These findings have important implications for tax authorities in efforts to increase taxpayer compliance through optimizing tariff policies, enforcing sanctions, and improving the quality of tax services.